Interferometric optical fiber sensor for optoacoustic endomicroscopy. Issue 7 (7th April 2021) - Ülgen, Okan; Shnaiderman, Rami; Zakian, Christian; Ntziachristos, Vasilis
Abstract: Optical fiber sensors can offer robust and miniaturized detection of wideband ultrasound, yielding high sensitivity and immunity to electromagnetic interference. However, the lack of cost‐effective manufacturing methods prevents the disseminated use of these sensors in biomedical applications. In this study, we developed and optimized a simple method to create optical cavities with high‐quality mirrors for acoustic sensing based on micro‐manipulation of UV‐curable optical adhesives and electroless chemical silver deposition. This approach enables the manufacturing of ultrasound sensors based on Fabry‐Pérot interferometers on optical fiber tips with minimal production costs. Characterization and high‐resolution optoacoustic imaging experiments show that the manufacturing process yielded a fiber sensor with a small NEP ( 11 mPa / Hz ) over a broad detection bandwidth (25 MHz), generally outperforming conventional piezoelectric based transducers. We discuss how the new manufacturing process leads to a high‐performance acoustic detector that, due to low cost, can be used as a disposable sensor. Abstract : This work presents a simple and effective procedure for creating micro‐resonators on optical fiber tips to produce optical ultrasound sensors for optoacoustic endomicroscopy applications. By following a cost‐effective approach, we developed a high‐performance fiber ultrasound sensor exhibiting a small noise‐equivalent‐pressure of 11 mPa / Hz over a detection bandwidth of 25 MHz. Low‐cost production and disposability of the sensor provides a solution to address sterilization requirements in clinical applications where cross‐contamination control is essential.